The Effect of Anti Masquito Electric Gas that Consist Allethrin That Influence The Weight and Colour of Rats Liver - nurmawanti, nurmawanti; Soekanto, Ayly (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2017)
The aim of this research is to know the influence of anti mosquito electric gas that consisted Allethrin to the weight and colour of the rats liver. This research used an experimental method with the post test onlyÂ  control group design.Â  The subject of this research is male rats weight of 150 grams each and total there was 24 rats that were divided to 4 groups. The first one, theÂ  control groups (PO) was not given any of the gas, the second one, group 1 (P1) was given the gas for 4 hours everday, the third one, groupÂ  2 (P2), was given for 6 hours and last, group 3Â  (P3) was given 8 hours everyday. After later, onÂ  30 Th day, the rats were terminated and being put in a surgery to remove their liver. This data was analyzed using SPPS for windows version 16. To see the differences in weight between the groups, it was analyzed using anova, andÂ  to obtain the discoloration of the rats liver was analyzed using Kruskal Wallis Test. From the statistic tests, it show that there is significant difference in weight and color of liver in the group that Î± â¤ 0,05. According Anova Test, it shows that there is a significant difference Î± = 0,034 and from Kruskal Wallis test Î± = 0,013. In the conclusion anti mosquito electric gas that consist Allethrin affects the weight and the color of rats liver.